MAPPING THE SCIENTIFIC LANDSCAPE OF HALAL CERTIFICATION: BIBLIOMETRIC ANALYSIS - Fitrianti; Syaakir Sofyan; Moh Anwar Zainuddin; Abdul Jalil; Nur Syamsu (Academic Bright Collaboration, 2026)
This study aims to map the scientific landscape of halal certification research and examine its publication development, thematic focus, and key contributors in the global halal literature. A bibliometric approach was used, drawing on Scopus-indexed journal articles retrieved using the keywords “halal certification” and “halal product certification.” After screening and removing duplicates, 142 relevant articles published between 2010 and 2025 were analyzed using the Bibliometrix R-package through the Biblioshiny interface. The results indicate rapid growth in research in this field, with an average annual growth rate of 19.24%, highlighting Indonesia and Malaysia as the most dominant contributors. The Journal of Islamic Marketing emerged as the most influential source, while author productivity remains concentrated among a small number of scholars. The novelty of this study lies in providing one of the earliest comprehensive bibliometric mappings of halal certification, using Scopus data and the Biblioshiny visualization tool. Future research should integrate additional databases and explore emerging themes, such as digital halal governance and consumer protection, to strengthen halal certification studies. This study presents the most extensive bibliometric review of halal certification research in the global halal literature, delivering the first dedicated Scopus-based mapping of publication trends, thematic evolution, and leading contributors while introducing a novel Halal Certification Research Landscape Framework.